Unleashing the Power of Reading: Effective Strategies for Non-Native Arabic Language Learners - Saepudin Saepudin; M. Taufiq Hidayat Pabbajah; Mustaqim Pabbajah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study addresses the pressing need for effective reading strategies among non-native Arabic language learners, who often encounter considerable obstacles in decoding and understanding Arabic texts due to the language’s complex morphology and diglossic nature. The main aim is to identify and classify strategic approaches that enhance Arabic reading proficiency and, in doing so, support broader language acquisition. Framed within the discourse of second language pedagogy, the research draws attention to the lack of focused studies on Arabic reading skills, emphasizing its theoretical and pedagogical significance. Using a systematic literature review, the study synthesizes findings from recent scholarship to evaluate cognitive, affective, and metacognitive strategies that benefit non-native learners. Results indicate that Direct Memory Strategies are essential for vocabulary retention and text recall, while Direct Cognitive and Compensation Strategies help bridge comprehension challenges. In addition, Indirect Cognitive, Affective, and Social Strategies contribute to learner motivation and collaboration, which are vital for maintaining sustained engagement with Arabic texts. These findings confirm that a multimodal strategic framework can meaningfully enhance Arabic reading competence as a second language. The study offers both theoretical insights and practical guidance for educators, curriculum developers, and policymakers working in Arabic language education.